Design of Animated Subject Materials in Integral Calculus Course - Shodikin, Ali; Novianti, Anik (Unnes Journal of Mathematics Education, 2017)
A pleasant learning environment is influenced by the teaching materials used. We arrange teaching materials in that can make learning more exciting and increase the learning interests of learners. Integral calculus is still one of the problem subjects for students and contains primary materials as a prerequisite for other courses. The design of the animated learning materials for the integral calculus course needs to be developed. The resulting product has different characteristics from other teaching materials, such as presentation design that emphasizes graphical animation, some material parts with simulation video, sample and practice questions. This teaching material is also equipped with a guidebook of its use. Animated teaching materials are expected to be an alternative solution in increasing students' interest and understanding in integral calculus courses.